Enchancing Sustainability: The Impact of Green Accounting Using Green Restaurant Indicators - HALIM, Ardinny Berlian; YANTIANA, Nella; MUHSIN, Muhsin (PT Keberlanjutan Strategis Indonesia, 2024)
Indonesia currently ranks fourth in the world's food waste production, with food waste accounting for 41.2% of total waste. This study evaluates the impact of implementing green accounting on the environmental performance of restaurants. Green accounting considers environmental aspects in financial statements, including a business's environmental impact, use of natural resources, and mitigation efforts. It includes using environmentally friendly materials, efficient waste management, and renewable energy in restaurants. The research was conducted at AE Kitchen & Dessert Restaurant in Pontianak using qualitative data from observation, interviews with the restaurant owner and four customers, and documentation. This restaurant has implemented green accounting well, and many green restaurant indicators have been implemented. The results showed that green accounting is essential in the restaurant industry to effectively manage environmental costs, reduce negative impacts, support sustainability, increase efficiency, and improve long-term business reputation. This research confirms that adopting green accounting is an important strategic step for the restaurant industry to reduce environmental impacts and ensure the sustainability of ecologically responsible operations.